Mobile Learning in Higher Education for The Industrial Revolution 4.0: Perception and Response of Physics Practicum - Darmaji, Darmaji; Kurniawan, Dwi Agus; Astalini, Astalini; Lumbantoruan, Artha; Samosir, Sofia Christine (International Journal of Interactive Mobile Technologies (iJIM), 2019)
Mobile learning is the use of technology in the learning process using tablets, PCs or smartphones. Online based mobile learning provides opportunities for students to study anytime and anywhere. The use of a website as a learning media gives users broad access without downloading additional applications that are burdensome to the device. Therefore, the perception of physics education students is needed on the use of mobile learning in basic physics practicum II at Universitas Jambi. This study aims to introduce new learning media that are more effective and flexible in the 4.0 digital era. Based on the results of the study, the perceptions of physics education study program students are in a good category with an average of 74.01 and a median of 75.00 and a mode of 75.00. Distribution of perception scores of physics education students has a minimum value of 52.00 and a maximum value of 91.00